2017
DOI: 10.1093/eurheartj/ehx394
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a targeted and testable antiarrhythmic therapy for long-QT syndrome type 2 using a patient-specific cellular model

Abstract: Lumacaftor, a drug already in clinical use, can rescue the pathological phenotype of LQT2 iPSC-CMs, particularly those derived from Class 2 mutated patients. Our results suggest that the use of LUM in LQT2 patients not protected by β-blockers is feasible and may represent a novel therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 34 publications
3
67
0
Order By: Relevance
“…In particular, iPSCs are not burdened by ethical issues and have been shown to differentiate into cardiac-like cells both in vitro and in vivo [15]. The characteristics of these cardiac cells are similar, but not identical, to human cardiomyocytes also in their ion channel apparatus, as demonstrated by disease-modeling studies [17,18]. Efforts to obtain standardized protocols to produce iPSC lines possibly committed toward cardiac lineage and to induce the maturation of iPSC-derived cardiomyocytes are needed.…”
mentioning
confidence: 99%
“…In particular, iPSCs are not burdened by ethical issues and have been shown to differentiate into cardiac-like cells both in vitro and in vivo [15]. The characteristics of these cardiac cells are similar, but not identical, to human cardiomyocytes also in their ion channel apparatus, as demonstrated by disease-modeling studies [17,18]. Efforts to obtain standardized protocols to produce iPSC lines possibly committed toward cardiac lineage and to induce the maturation of iPSC-derived cardiomyocytes are needed.…”
mentioning
confidence: 99%
“…Additionally, molecular characterization of the LQT2 hiPSC‐CM models has confirmed that many KCNH2 missense mutations result in a trafficking defect of the ion channel . Recently, Lumacaftor, a drug known to act on channel trafficking and approved for treating cystic fibrosis, was shown to restore trafficking of the ion channel in LQT2 hiPSC‐CMs but only for certain mutations . Excitingly, the first attempt to validate these findings in two of the patients whose hiPSC‐CMs had shown a response, indicated a significant shortening of their QTc interval when they were also treated with the corresponding clinically approved compound .…”
Section: Hpsc Models Of Inherited Cardiac Diseasesmentioning
confidence: 92%
“…23,24 Recently, Lumacaftor, a drug known to act on channel trafficking and approved for treating cystic fibrosis, was shown to restore trafficking of the ion channel in LQT2 hiPSC-CMs but only for certain mutations. 25 Excitingly, the first attempt to validate these findings in two of the patients whose hiPSC-CMs had shown a response, indicated a significant shortening of their QTc interval when they were also treated with the corresponding clinically approved compound. 26 These findings emphasize the importance of understanding the complex interplay between an aberrant genotype and molecular phenotype to pave the way for more personalized medicine.…”
Section: Significance Statementmentioning
confidence: 94%
“…Cardiomyocytes derived from human induced pluripotent stem cells (hiPSCs) are now wellestablished as models for LQT2 [15][16][17][18] . Indeed, a number of hiPSC lines have been derived from both symptomatic and asymptomatic patients with mutations in various regions of hERG 19 .…”
mentioning
confidence: 99%